Use of bilateral superficial gluteal muscle flaps for the repair of ventral perineal hernia in dogs: A cadaveric study and short case series. Issue 8 (15th June 2020) - Bitton, Erez; Keinan, Yael; Shipov, Anna; Joseph, Rotem; Milgram, Joshua
Abstract: Objective: To describe bilateral mobilization of the superficial gluteal muscle (SGM) to treat ventral perineal hernias in dogs. Study design: Cadaveric study and short case series. Sample population: Male dog cadavers (n = 10) weighing between 5 and 42 kg and three dogs treated for ventral perineal hernia. Methods: Cadavers were positioned in right and left lateral recumbency to free the origin and insertion of the ipsilateral SGM except for muscle fibers originating on the first tail vertebra and sacrotuberous ligament. The dogs were placed in ventral recumbency to approach the perineum and rotate the muscle flaps. The insertions of the SGM were sutured together ventral to the anal sphincter muscle. The dorsal border of the overlapping tendons was sutured to the anal sphincter muscle, and the ventral border was sutured to the ischiourethralis muscle. The amount of overlap between bilateral flaps was measured. The SGM flaps were used to revise recurrent perineal hernias in three dogs. Results: Superficial gluteal muscle flaps were created without damage to the blood supply in all dogs. The overlap between the bilateral flaps ventral to the anal sphincter measured 0 to 2.4 cm. No recurrence was detected at follow‐up (6‐12 months) in the three dogs treated with these flaps. Conclusion: Superficial gluteal muscle flaps were mobilized without damage to the blood supply and crossed the midline ventral to the anal sphincter. Flaps were used successfully to repair ventral perineal hernias in three dogs. Clinical significance: Bilateral SGM flaps can be considered to repair ventral perineal hernias.